Neural Network Model of Energy Saving of Combined Drum Dryer (Texas Journal of Engineering and Technology, 2023)
This article is devoted to the construction of a neural network model for predicting the electricity consumption of a combined dryer. The neural network model was carried out in the Neural Networks Toolbox package in Matlab. The adequacy of the built model was determined and compared with the experimental results.